Gemological modification of local natural gemstones by ion beams - S. Intarasiri (2018)
Ion implantation was applied as an effective method to gemological modification of Thai local natural corundum including sapphire and ruby for enhancement of the essential qualities of the gemstones. Oxygen and nitrogen ions at medium and low energies to various fluences were implanted to the natural gemstones. The heavy ion irradiation modifies the color to desirable colors and improves the color distribution, transmission and lustre. These modifications lead to the improvement of quality of gemstones and thus the market value. Possible mechanisms of these modifications have been proposed. The main cause for these modifications could be the changes in oxidation states of impurity metals, induction of charge transfer from one metal cation to other and the production of color centres. © 2009 Elsevier B.V. All rights reserved.